Analisis Hambatan Pelaksanaan Ekstrakurikuler Pramuka Sekolah Dasar Di Kabupaten Bandung - Denis Desfriyati; Mustika Khoirunnisa Kholillah; Nurassyifa Qurotul Aini; Randita Lestari (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Every activity is bound to be presented with obstacles, this research describes the obstacles to the solutions suggested by the researchers. Based on the research results, extracurricular activities are divided into 2 (two) parts, namely mandatory and optional extracurricular activities. This is in the Minister of Education and Culture Regulation Number 63 of 2014 concerning extracurricular activities in educational units. One of the extracurricular activities that must be implemented at every level is the Scout Education extracurricular as implemented in the 2013 curriculum. Scout Education plays a role as a vehicle for complementary activities in the learning process with the aim of forming and developing student character. In the implementation of Scout Education extracurricular activities there are 3 (three) models, namely the Block Model, Actualization Model and Regular Model. This research method uses a descriptive qualitative method, namely the research results are presented descriptively.